(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2001)
Investigation of antioxidant properties of some herbs was carried out. Efficiency of herbs as antioxidants was tested by the influence of their extracts on the intensity of spontaneous chemiluminescence and by the change of the level of the malonic dialdehyde in the model system. The obtained results indicate that all experimented extracts show antioxidant properties in different degrees.